ANALISIS PENGARUH MOTIVASI KONSUMEN, PERSEPSI KUALITAS DAN SIKAP KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN PRODUK EIGER DI KOTA SEMARANG - Kurniawati, Desi; Wahyuningsih, Susanti (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2022)
This study aims to determine whether Consumer Motivation, Perceived Quality, and Consumer Attitudes influence the Eiger Product Purchase Decision in Semarang City. The population in this study are Eiger Product Users in Semarang City. Sampling was carried out using purposive sampling method and the number of samples was 96 respondents. The type of data used is primary data. This study uses a questionnaire in collecting data. The test techniques used are validity test, reliability test, classic assumption test including normality test, multicollinearity test, and heteroscedasticity test. Hypothesis testing in this study used multiple linear regression analysis and hypothesis testing with the help of SPSS version 23. The results of this study indicate that Consumer Motivation has a significant positive effect on Purchasing Decisions. This is evidenced by a significance level of 0.00 <0.05 while tcount is 4.918 > 1.66159, it can be concluded that H1 is accepted. Perceived quality does not affect purchasing decisions. This is evidenced by the significance level of 0.520 > 0.05 while the tcount is 0.645 <1.66159, it can be concluded that H2 is rejected. Consumer Attitude has a significant positive effect on Purchasing Decisions. This is evidenced by a significance level of 0.00 <0.05 while tcount is 5.071 > 1.66159, it can be concluded that H3 is accepted. Consumer Motivation, Perceived Quality, and Consumer Attitudes simultaneously have a significant effect on Purchasing Decisions. This can be seen from the Fcount value which is 74.719 which is smaller than the Ftable value which is 2.70, while with a significance value of 0.000 which is smaller than the significance value below 0.05.Keywords: Consumer Motivation, Perceived Quality, Consumer Attitudes, and Purchase Decisions.